Garbhagriha (sanctum sanctorum) of the Sheshashayi Temple - Temples of India Project Team (Jio Institute, 2024)
Close view of the garbhagriha (sanctum sanctorum) of the Sheshashayi Temple (Temple 2), Baroli group of temples.